Analysis of Investment Feasibility of Fishery Product Diversification as Economic Strengthening of the Outermost Islands of Indonesia's Border (Case Study of Rupat Island and Bengkalis Island) - Pratama, Adrian Irnanda; Rosa, Nageeta Tara; Arif, Muhammad (Inovbiz: Jurnal Inovasi Bisnis, 2024)
This study aims to determine the feasibility study of fish-based processed products caught by fishermen on Bengkalis Island and Rupat Island as one of the islands included in the category of Border Islands. In this study, several aspects of the feasibility study were examined which included aspects of market feasibility and marketing (product quality and taste, determination of processed product users and market maps and customer needs for products), production aspects (type of production, production capacity and use of technology) and aspects of financial (investment and economy). trials for making products using lomek fish (Harpodon nehereus), biang fish (Ilisha elongata) and gonjeng fish (Coilia mystus) with processed products that have been successfully produced are dimsum, chips, otak-otak, meatballs and nuggets. The results of this study indicate that the quality and taste of nugget products using the organoleptic and hedonic tests of the resulting product obtained for the aroma indicator is in the 3.61 interval range with the delicious/fragrant category, then for the taste indicator in the delicious category with an interval value of 3.70. Furthermore, the panelist's assessment of product texture was at an interval of 3.35 with the soft/soft category and for the color of the panelists gave an interval of 2.80 with a slightly appetizing category. Likewise with other products, the results of the organoleptic and hedonic tests showed that the panelists received and gave good responses to each test in the available indicators. The overall financial feasibility aspect of the product is feasible to run and develop more optimally, as seen from the R/C>1 test results. This research is expected to bring up new business opportunities that can help improve the welfare and improve the economy of the people in the outermost island areas of Indonesia's borders